Do women's attitudes towards abortion and contraceptive methods influence their option for sterilization? - Elisabeth Meloni Vieira
This paper analyzes the attitudes of low-income women towards abortion and contraception. A survey was conducted in 1992 with a total of 3,149 childbearing-age women living on the outskirts of the Greater Metropolitan São Paulo Area. The study focuses on a sub-sample of 583 women. Attitudes of sterilized and non-sterilized women are compared. Women, especially those sterilized, found the most important attribute of a contraceptive method to be its effectiveness. Women currently taking the pill were less likely than those sterilized to agree that sterilization was the best method because of its effectiveness. Sterilized women were less likely than non-sterilized women to trust the pill. Sterilized women were more likely than non-sterilized to have reported adverse effects from the pill. Most women found abortion unacceptable except in the case of risk to the woman's life. Women using more effective methods showed stronger negative attitudes towards abortion. The tendency to be sterilized while still young was associated with more negative attitudes towards abortion. Family planning activities in basic health care services should include individual counseling for contraceptive use.